Aura of night - Graham, Heather (Graham, Heather. Krewe of hunters series, 2022)
"True evil never dies. It only waits in the dark. All book editor Megan Law wants is to bury the memory of her brutal kidnapping and move on with her life. So when her publisher asks her to spin her hellish experience into the next bestseller, Megan agrees only because it might help keep other women safe. Then a mysterious, gruesome package arrives in the mail--a reminder that the nightmare isn't over just yet. FBI investigator Ragnar Johnson is running out of time. He knows in his gut there's more to the recent Embracer killings, and he needs Megan's help. Even with their rocky past behind them, working together now isn't going to be easy. But when things take a deadly turn, Megan and Ragnar discover a deep connection that they'll have to use, because something is trying to tear them apart ... forever"--Dust jacket flap.